lmplementasi Emotional Intelligence Dalam Pelaksanaan Supervisi Pengajaran Kepala Sekolah Untuk Meningkatkan Semangat Kerja Profesional Guru - Ali, Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
One of the principal's responsibility toward teacher is improving teachers' capability in managing teaching learning process in the school. Therefore, he must hold supervision perfectly. In fact, in many cases indicate that the principal, in general, who holds the duties of supervision in the school were not inherent with the principles of supervision yet. The methods used by the principal were less persuasive, whereas the appropriate method can determine the success supervision, because the activities of supervision are related with social interaction between supervisor and teachers. This article describes about individual's emotional intelligence that has influence in achieving the goals. Someone who has a high emotional intelligence is more successÂ in his works, can develop a good personal relation, and motivate other people and himself The principal's emotional intelligence has influence toward achievement of his works significantly. The principal who has a high emotional intelligence is more success in holding supervision and duties, can develop a personal-interpersonal relations and motivate the teachers and himself well.